Migração em tempo: influência dos pesos para compensação de amplitude - FERREIRA, Adriano Silva (2019)
Automatic methods for velocity model building using pre-stack migration perform better if the amplitude of events in common image gathers are equalized. For velocity analysis in time, the choice of the weight function in the Kirchhoff migration operator controls the amplitude of the migrated events. Numerical experiments evaluating five different weight functions indicate that good amplitude equalization can be achieved using approximations to weight functions derived from true amplitude Kirchhoff migration. Effective equalization of amplitudes in CIGs can also be achieved through a simpler and computionally cheaper weight function, which compensates for the obliquity factor only.